Avaliação da osseointegração de implantes dentários na reabertura precoce: estudo clínico preliminar - Rezende, Rodrigo Oliveira Burlamaqui de (2016)
Currently early or immediate aesthetic and fnction are the main concer between professional and patients who planned oral rehabilitation.The classical two stages protocol of dental implants can be effectively replaced by immediate loading safely with predictable results after improvements of dental implants systems.To validate and confirm these improvements achieved after pre-clinical studies,the present study assess clinically,the early loading of dental implants.Ten patients were submitted to unit or multiple implant placement in a total of 28 implants.After 60 days the implants were loaded regardless of initial torque at placement.Mechanical testing was performed using the torque for prosthetic abutment placement as a success criteria of osseointegration.Descriptive analisys was performed and the overall success rate was 92.85%.The present protocol can be a reliable and safe for early loading for oral rehabilitation.Larger samples are necessary to confirm the preliminary results.